Study of combination capability and hybrid power and estimation of the dominance degree and inheritance in bread wheat (Triticum aestivum L) - Ibtesam Nadhem Alassaf (College of Education for Pure Sciences, 2010)
ABSTRACT Five varieties of bread wheat along with their (10) hybrids from half diallel crosses were used to study combining ability, heterosis, heritability and average degree of dominance for biological yield, five spike weight, resistant to lodging, harvesting index and straw weight. The result showed that the (GCA) and (SCA) variances were significant for the studied characters. The ratio between the variance component of (GCA) and (SCA) was less than one for all studied characters, which indicates the presence of additive and non-additive gene effects on all the studied characters and the non additive gene effect is more important for determining these characters. Desirable and significant heterosis was observed for some hybrids. Were the broad sense heritability and narrow sense heritability low for all characters? There were over dominance for spike weight, harvesting index, resistant to lodging and straw weight and partial dominance for biological yield.